DEFECTS, DEFECT ORDERING, STRUCTURAL COHERENCE AND SUPERCONDUCTIVITY IN THE 123-COPPER OXIDES - Jorgensen, J; Hinks, D; Radaelli, P; Pei, S; Lightfoot, P; Dabrowski, B; Segre, C; Hunter, B (1991)
We discuss the influence of oxygen defects and defect ordering on superconductivity in 123 compounds. Because of the complexity of the high-temperature phase diagram, the synthesis history can significantly influence the properties. Room-temperature annealing experiments show that defect ordering on a short length scale can have a remarkable affect on superconductivity. We propose that structural coherence in the CuO2 planes, which is present only if there is orthorhombic symmetry on at least a short length scale, is a requirement for superconductivity in these compounds. © 1991.